Principles and features to define and describe arts interventions for people with dementia: a qualitative realist study. Issue 3 (2nd September 2019) - Cousins, Emily; Tischler, Victoria; Garabedian, Claire; Dening, Tom
ABSTRACT: Background : There is currently no consensus regarding the definition and description of arts interventions for people with dementia. Developing a common language of classification will encourage reflection on artistic practice, support the evaluation and improvement of arts interventions, and enable their benefits to be communicated more effectively. Methods : Using a qualitative framework derived from taxonomy and realist methodology, a literature review was undertaken to identify what key principles underpin arts interventions. This analysis was complemented by focus groups and workshops incorporating the lived experience of carers, artists, practitioners and care staff. Results : Nine principles were identified as elements present in person-centred arts interventions for people with dementia: Animation, Transcendence, Selfhood, Humanity, Expression, Connection, Possibility, Involvement and Awareness. Conclusions : It is possible to identify the component parts of arts interventions for people with dementia. These principles form an empirical basis for understanding how arts interventions work, while still respecting their individual nature.